Incidence and predictors of opportunistic infections among HIV-infected children on antiretroviral therapy at public health facilities of Southwest Ethiopia People Regional State, 2023: a multicenter retrospective follow-up study - Nigatu Admasu; Mohammed Jihad; Abeje Kebede; Masrie Getnet (BMC, 2024)
Abstract Background Opportunistic infections (OIs) pose a significant threat to children infected with HIV. Despite advancements in antiretroviral therapy (ART), these infections continue to be a public health concern. However, there is limited evidence regarding the incidence and predictors of OIs among HIV-infected children in Ethiopia, particularly in the study area. Therefore, the objective of this study was to assess the incidence and predictors of OIs among HIV-infected children on ART at public health facilities of Southwest Ethiopia People Regional State. Methods The study employed an institution-based retrospective cohort design, conducted from July 1, 2018 to July 31, 2023, among HIV-infected children aged less than 15 years. Data were extracted using the national ART intake and follow-up forms. KoboCollect version 2023.2.4 and STATA version 14.0 were used for data collection and analysis, respectively. The Kaplan-Meier survival curve was used to estimate the probability of OI-free survival time. Variables with P-value < 0.25 in the bivariable Cox proportional hazard model were selected as candidates. In multivariable analysis, P-value < 0.05 and adjusted hazard ratio (AHR) with 95% confidence interval (CI) were used to declare statistically significant predictors. Results Of the total 409 HIV infected children, 122(29.8%) developed at least one OI, contributing to 954.95 person-years of risk. The overall incidence rate was 12.8 (95% CI: 10.7, 15.2) per 100 person-years. The OI-free survival probability at the end of the follow-up period was 0.277(95% CI: 0.139, 0.434). The commonest OI was pulmonary tuberculosis, 30.33% (95% CI: 22.7, 39.2). Non-disclosing HIV status (AHR: 2.56, 95% CI: 1.42, 4.63), children aged 10-14 years (AHR: 2.34, 95% CI: 1.10, 4.95), no history of prevention of mother-to-child transmission of HIV (AHR: 2.33, 95% CI: 1.48, 3.66), hemoglobin level < 10 mg/dL (AHR: 2.26, 95% CI: 1.37, 3.75), fair or poor adherence to ART (AHR: 1.74, 95% CI: 1.09, 2.79), and having past history of OIs (AHR: 1.61, 95% CI: 1.03, 2.55) were statistically significant predictors of OIs. Conclusion and recommendations The incidence of OIs was high in the study area. Hence, health facilities need to regularly monitor hemoglobin, enhance ART adherence, provide OI prophylaxis for at-risk children, reinforce PMTCT programs for early OI detection and management, and encourage timely and age-appropriate HIV status disclosure. Caregivers of HIV-infected children are also required to oversee and assist their children in adhering to the ART.